Combustíveis para ADS - Graiciany de Paula Barros (2014)
Accelerator Driven Systems (ADS) are subcritical hybrid systems in which charged particles produced by an accelerator are used to induce spallation reactions in some target material, resulting in the production of neutrons that are used in a subcritical reactor core to maintain the fission chain. These systems have been studied for transmutation of nuclear waste and for thorium regeneration. However, there is a difficulty in the use of thorium in ADS , which is the need to adding some fissile isotope (233U ou 235U) to reach the criticality necessary. This addition of fissile isotopes of uranium is not a good option due to its technological difficulties and waste generation inherent in every enrichment process. The addition of 233U is even more problematic, since this isotope needs to be generated from 232Th. One option for the use of thorium without the addition of 233U consists in using thorium with nuclear waste from conventional reactors. In this context, the aim of this work is to establish a fuel configuration which simultaneously turns possible the thorium regeneration and the incineration of spent fuel. In order to simulate the neutronic aspects of the studied fuels, the computational codes MCNPX 2.6.0 (MCNPX/CINDER) and Monteburns 2.0 (MCNP5/ORIGEN 2.1) were used. The results indicate a possible configuration of ADS fuel that allows regeneration of thorium and incinerating radioactive waste.